MiR-942 regulates the function of breast cancer cell by targeting FOXA2 - Zhang, Jinku (Biosci Rep, 2019)
MicroRNA (MiR)-942 regulates the development of a variety of tumors, however, its function in breast cancer (BCa) has been less reported. Therefore, the present study investigated the regulatory effects of miR-942 on BCa cells. The expression of miR-942 in whole blood samples and BCa cell lines was detected by quantitative real-time (qRT)-PCR. Direct target gene for miR-942 was confirmed by dual-luciferase reporter assay. FOXA2 expression in adjacent tissues was detected by qRT-PCR. The effects of miR-942, or miR-942 with FOXA2, on the cell viability, proliferation, apoptosis, migration and invasion of BCa cells were determined by cell counting kit-8 (CCK-8), colony formation assay, flow cytometry, wound scratch and Transwell, respectively. The levels of N-Cadherin, E-Cadherin and Snail were determined by Western blot. Kaplan–Meier was used to explore the relationship among the expressions of miR-942 and FOXA2 and the prognosis of BCa patients. MiR-942 had high expressed in BCa, while its low expression significantly suppressed the cell viability, proliferation, migration and invasion of BCa, but increased cell apoptosis. Down-regulation of N-Cadherin and Snail and up-regulation of E-Cadherin were also induced by low-expression of miR-942. FOXA2, which was proved as the direct target gene for miR-942 and was low-expressed in BCa, partially reversed the effect of overexpressed miR-942 on promoting cell viability, proliferation, migration and invasion, and suppressed cell apoptosis. A lower survival rate was observed in BCa patients with a high expression of miR-942 and a low expression of FOXA2. MiR-942 promoted the progression of BCa by down-regulating the expression of FOXA2.